Meeting the needs of multimorbid patients with Type 2 diabetes mellitus – A randomized controlled trial to assess the impact of a care management intervention aiming to improve self-care. (April 2019) - Kamradt, Martina; Ose, Dominik; Krisam, Johannes; Jacke, Christian; Salize, Hans-Joachim; Besier, Werner; Mayer, Manfred; Szecsenyi, Joachim; Wensing, Michel
Abstract: Aims: This study explored the impact of a care management intervention aiming to improve self-care behavior in multimorbid individuals with Type 2 diabetes mellitus on health-related quality of life (HRQoL). Methods: A patient-level randomized parallel-group superiority trial with 32 primary care practice teams, 11 care managers and 495 patients was conducted. The intervention was delivered as add-on to an already implemented disease management program and embedded in a network of primary care practices. Hierarchical linear modeling was used to analyze impacts of the care management approach on HRQoL. Results: Small improvements of HRQoL in the intervention arm were found after nine months ( r  = 0.024; 95%CI = [0.000, 0.047]). However, compared to standard care no significant differences of HRQoL changes were observed ( r  = 0.022; 95%CI = [−0.011, 0.054]). Subgroup analyses showed effects for female participants favoring the intervention arm ( r  = 0.059; 95%CI = [0.010, 0.108]). No significant differences between intervention and control arm for several other subgroups were observed, including subgroups defined by comorbidities. Conclusion: Additional care management did not influence HRQoL over and above standard disease management. Improving diabetes patients' self-care behavior in the context of structured disease management programs may be difficult to achieve. Women might benefit from additional care management, but this finding needs to be confirmed in future research.